Integrating PROPER, Adipura dan SDGs: A Study of Sustainability Governance in Indonesia - Axsal; Monoarfa, Winarni; Idrus, M. Rijal; Daud, Anwar; Demmalino, Eymal Bahsar; Darhamsyah (Journal of Cultural Analysis and Social Change, 2025)
The environmental pillar of the Sustainable Development Goals (SDGs) is increasingly important in Indonesia due to rapid urban growth and expanding corporate activities. Two major national programs—PROPER (corporate environmental performance rating) and Adipura (urban environmental award)—directly contribute to achieving SDG goals 6, 11, 12, 13, 14, and 15. This study uses bibliometric analysis and systematic meta-synthesis to examine how these programs relate to the environmental SDGs. The analysis shows that from 2015 to 2024, most studies discussed PROPER, Adipura, or SDGs separately, with little effort to integrate them. To address this gap, the study proposes an integrative framework called “PROPER Achievements, Adipura Awards, and Sustainable Cities”, which connects corporate and local government initiatives to improve environmental governance, strengthen community participation, and accelerate progress toward the environmental SDGs in Indonesia.